STRATIGRAPHIC AND CHRONOLOGIC FRAMEWORK OF THE UPPER MIOCENE CESSANITI SUCCESSION (VIBO VALENTIA, CALABRIA, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
This study revises the mammal-bearing stratigraphic succession of Cava Gentile, near Cessaniti (Calabria, southern Italy), with the aim of dating the Late Miocene fossiliferous succession by the integration of mammal biochronology with sedimentology, magnetostratigraphy and marine biostratigraphy. Since the first discovery of mammal remains at Cessaniti, the chronological framework of the sedimentary succession was based on the biochronological significance of the mammal assemblage and on the biostratigraphic characterisation of the capping unit. Chronological control of the sedimentary succession and the age range of the mammal faunal assemblage at Cessaniti is now possible by combining the mammal biochronological constraints with biostratigraphy and the characterisation of the magnetostratigraphy of the sedimentary succession. Our study allows the conclusion that: i) an overall transgressive trend is recorded at the late Tortonian succession of the Capo Vaticano area, with locally different depositional trends; ii) the late Tortonian transgression was punctuated by minor episodes of forced regression, as attested by soils and fluvial deposits intercalated within the Cava Gentile succession (documented here for the first time); iii) the relative sea level rises that characterised these sedimentation patterns allowed accumulation of marine and terrestrial fossils in specific transgressive horizons; iv) the combination of palaeomagnetic data and biostratigraphic analyses, together with the biochronological constraints offered by the Cessaniti mammal assemblage, allows the assignment of the basal unit of the Cessaniti (Cava Gentile) succession to the normal Chron C4n (8.1–7.5 Ma); and v) the maximum range of the Cessaniti land mammal assemblage from Cava Gentile is about 1 Ma, bracketed between 8.1 and 7.2 Ma.